If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-10=2(2x+12)
We move all terms to the left:
4x-10-(2(2x+12))=0
We calculate terms in parentheses: -(2(2x+12)), so:We get rid of parentheses
2(2x+12)
We multiply parentheses
4x+24
Back to the equation:
-(4x+24)
4x-4x-24-10=0
We add all the numbers together, and all the variables
-34!=0
There is no solution for this equation
| 4x+16+2x+5=53 | | -32=2(q-96) | | 4x+16+2x+5=23 | | P=30+6x | | 9x+1=9x | | -4x=10x+10 | | 3x-3=77 | | g/8+36=38 | | -3x+3=-7x-41 | | 31-(2c+4)=2(c+6)=c | | -2(x-9)=6 | | 31-(2c+4)=2(c=6)=c | | -3x+3=-7-41 | | x−5x=16 | | 5a/7=2 | | (a+3)(a-8)=0 | | 53=n/10+55 | | 30x+270=450 | | 2(m=30=24 | | 6x-(6x+4)=1 | | 4x-61=34 | | 24-3w=3 | | x2=160 | | 71=9g+8 | | 6x-6x+4=1 | | 5=m4 | | 5(w-76)=35 | | 3x+1=5x=5 | | 2n+33/4=8 | | v=4v-78 | | 3w-11=-16 | | 42x-24= |